THE ROLE OF MUSIC CULTURE IN THE DEVELOPMENT OF MAN IN EVERY WAY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides an overview of the role and importance of music in the evolution and development of humankind. The information provided, in turn, is enriched with music by our great ancestors, such as Ibn Sina, Alisher Navoi, Al-Farabi.